SOCIAL AND ECONOMIC VALUATION OF MANGROVE FOREST ECOSYSTEM IN NORTH BUTON REGENCY, SOUTHEAST SULAWESI PROVINCE - Firman Syah; Leti Sundawati; Bahruni Bahruni (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2019)
Mangrove forest is the main life-supporting ecosystem which is important for coastal and marine areas that haveeconomic function as well spawning ground for living things. This study aims to analyze the community perceptionas well as to find out the economic value generated from mangrove ecosystem in Kalibu and Eelahaji villages,North Buton Regency. The study used purposive sampling method with the 50 respondents from both villages thatwere chosen in purposively.  The results showed that ccommunity perceptions to the benefit of mangrove forestsand forest protection in the Kalibu and Eelahaji vilages were still in high category. According to the communityperception, the main cause of mangrove forest degradation was due to  mangrove wood collection for fire wood.Economic valuation is an effort to provide quantitative value of goods and services provided by natural resourcesand environment in the form of direct use value, indirect use value, and option value. The direct value of mangroveforest benefit consists of fire wood, fish, crab, and shrimp. Indirect use value of mangrove forest is in the form ofbarrier to abrasion and sea- water intrusion while the option value is in the form of ecotourism. The quantificationof all economic values from mangrove of Kalibu village results in IDR 8,680,773,742 per year while in Eelahajivillage is IDR 6,144,339,375 per year.